PERAN ASISTEN GURU (TEACHING ASSISTANTS) DALAM MAKSIMALISASI PROSES PEMBELAJARAN DI KELAS - Selly Nurina Suraya (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2013)
A teacher is oblidged against all learning development of the students, in achievement, health, savety and well-being. Class instruction has forbit teacher to do all types of physical harashment, discrimination and careless conduct against the physical-impaired students. Teacher assistant is a person who helps and supports the teacher in classes during the teaching-learning process. In England, he / she is called as teaching assitants, classroom assistants, learnong support assistants, child support assistants or Special Needs Assistants. Both, the teacher and the Special Needs Assistants are oblidged to collaborate to carry out teaching which can serve the students’ diversity in each group of the class by applying instruction which is rooted from the students’ diversity.